FIGURE OF SPEECH TRANSLATION OF NOVEL TUESDAYS WITH MORRIE MITCH ALBOM WORKS BY ALEX TRI KANTJONO WIDODO CONTENT ANALYSIS RESEARCH - Ahmad Efendi (Journal of English Educational Study (JEES), 2019)
This research generally aims to increase knowledge of the translation of a novel translation. Specifically to determine equivalence translations figure of speech, to know the techniques translation in translations figure of speech, and meaning shift of translations figure of speech in this novel Tuesdays with Morrie. The object of research is novel translation by Alex Tri Kantjono Widodo with the title Tuesday with Morrie Mitch Albom's work.The method used is qualitative method and the technique used is content analysis. Data collected by reading novels, collecting data by selecting a clause or sentence containing a figure of speech, quote them and identify then create a table. Furthermore, the sentences were analyzed by formal equivalence or dynamic equivalence.There are 87 identified sentences as a sentence containing a figure of speech. Sentences are divided into two correspondences that formal and dynamic equivalence. There were 70 sentences, or 80% containing formal equivalence and 17 sentences or 20% containing dynamic equivalence. Later, it was discovered seven translation techniques used by the translator of the novel Tuesday with Morrie. Finally, there are 3 meanings shift in translations figure of speech. Keyword: Figure of Speech, Content Analysis, Translation, Equivalence, Qualitative, Technique, Meaning Shift.